2016
DOI: 10.1371/journal.pone.0146719
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Differences between Two Optical Isomers of Radioiodinated o-iodo-trans-decalinvesamicol for Use as a Radioligand for the Vesicular Acetylcholine Transporter

Abstract: PurposeTo develop a superior VAChT imaging probe for SPECT, radiolabeled (-)-OIDV and (+)-OIDV were isolated and investigated for differences in their binding affinity and selectivity to VAChT, as well as their in vivo activities.ProceduresRadioiodinated o-iodo-trans-decalinvesamicol ([125I]OIDV) has a high binding affinity for vesicular acetylcholine transporter (VAChT) both in vitro and in vivo. Racemic [125I]OIDV was separated into its two optical isomers (-)-[125I]OIDV and (+)-[125I]OIDV by HPLC. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…D , c = 2.08, chloroform), respectively. These results showed that optical separation of OMDV was performed successfully, which is similar to the previously reported optical separation of o-iodo-trans-decalinvesamicol (OIDV) (Uno et al, 2016). (−)-OMDV showed five times higher binding affinity for VAChT than (+)-OMDV.…”
Section: In Vitro Competitive Binding Studysupporting
confidence: 88%
See 1 more Smart Citation
“…D , c = 2.08, chloroform), respectively. These results showed that optical separation of OMDV was performed successfully, which is similar to the previously reported optical separation of o-iodo-trans-decalinvesamicol (OIDV) (Uno et al, 2016). (−)-OMDV showed five times higher binding affinity for VAChT than (+)-OMDV.…”
Section: In Vitro Competitive Binding Studysupporting
confidence: 88%
“…imaging probe, PET, VAChT, vesamicol analog (Bar & Parsons 1986;Marshall & Parsons 1987), many vesamicol analogs have been developed as potential VAChT imaging agents for PET or SPECT (Azim et al, 2014;Bando et al, 2001;Barthel et al, 2015;Custers, Leysen, Stoof, & Herscheid, 1997;Efange, Michelson, Khare, & Thomas, 1993;Efange et al, 1994, Efange et al, 2000Kitamura et al, 2016;Kozaka et al, 2014;Mulholland et al, 1998;Shiba, Mori, & Tonami, 2003;Sorger et al, 2000Sorger et al, , 2008Sorger et al, , 2009. Furthermore, several reported vesamicol analogs were separated into optical isomers to improve in vitro and in vivo characteristics as VAChT imaging agents (Efange et al, 1994;Jung, Van Dort, Gildersleeve, & Wieland, 1990;Kovac et al, 2010;Li et al, 2013;Mulholland et al, 1998;Shiba et al, 2003Shiba et al, , 2009Tu et al, 2009Tu et al, , 2015Uno et al, 2016). However, many of the reported vesamicol analogs were shown to be insufficient for use as VAChT imaging probes because of binding to sigma receptors (σ1 and σ2) or low accumulation in the brain in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The rat brain uptake of (−)-[ 123 I]OIDV ( 13 ) was decreased by 71–73% by coadministration of (−)-[ 123 I]OIDV ( 13 ) with vesamicol (0.25 μ mol). (−)-[ 123 I]OIDV ( 13 ) was distributed in characteristically VAChT-rich regions, such as the cortex, striatum, diagonal band, amygdaloid nucleus, and trigeminal and facial nucleus [ 65 , 66 , 77 ].…”
Section: Vacht Imaging Agent Based On Vesamicol Analogsmentioning
confidence: 99%
“…Decalinvesamicol ((−)-OIDV ( 13 ) [ 66 ], OBDV ( 14 ) [ 67 ], and OMDV ( 15 )) [ 68 ] showed a higher affinity to VAChT than morpholinovesamicol analogs (FAMV ( 16 ) and FBMV ( 17 )). On the contrary, morpholinovesamicol analogs showed a higher selectivity to VAChT affinity than decalinvesamicol.…”
Section: Vacht Imaging Agent Based On Vesamicol Analogsmentioning
confidence: 99%